2018
DOI: 10.1364/oe.26.031829
|View full text |Cite
|
Sign up to set email alerts
|

Whispering gallery mode micro resonators for multi-parameter sensing applications

Abstract: A novel fiber optic sensing configuration for simultaneously measuring ammonia vapor (NH 3) concentration and relative humidity (RH) in air is proposed and experimentally demonstrated. The system comprised two silica whispering gallery mode (WGM) microsphere resonators coated with different polymer layers. One of the microspheres was dip-coated with sol gel silica polymer and another with a 0.5 % wt./vol. agarose hydrogel. WGMs in both microspheres were excited simultaneously by evanescent coupling using a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Optical microspheres are used extensively for temperature, humidity, and stress sensing. The working principle of microsphere resonators sensor is that the resonant wavelength or intensity of the output signal varies with the change in external environment .…”
Section: Structure and Application Of Wgmrsmentioning
confidence: 99%
See 3 more Smart Citations
“…Optical microspheres are used extensively for temperature, humidity, and stress sensing. The working principle of microsphere resonators sensor is that the resonant wavelength or intensity of the output signal varies with the change in external environment .…”
Section: Structure and Application Of Wgmrsmentioning
confidence: 99%
“…On this basis, members of the same group used a single tapered fiber coupled with two functionalized microspheres on different surfaces, and simultaneously measured ammonia (NH 3 ) concentration and RH. The results of the experiments showed that the sensitivity of the sensor array to ammonia was 19.07 pm ppm −1 and to RH was 1.07 pm %RH −1 . Most experiments are based on polymer coating.…”
Section: Structure and Application Of Wgmrsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the WGM sensor must address an open challenge to achieve the multi-parameter detection ability for practical applications [3,[34][35][36]. Although a micro-ring resonator biosensing array is exploited to realize multi-parameter biosensing using wavelength division multiplexing technology [37][38][39][40][41][42], its complexarray structure and detecting cost hinder its further development. Hence, it is critical for WGM sensors to exploit a universal multi-parameter detection mechanism with low detection complexity.…”
Section: Introductionmentioning
confidence: 99%